Hubungan Kausalitas Pertumbuhan Ekonomi Dengan Investasi di Kota Pontianak Kajian Model Granger - Jamaliah, Jamaliah (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
This study aims to examine and analyze the causality relationship between economic growth and investment, in this case private investment in the city of Pontianak. The data used is time series data for 15 years (2000 - 2015), to qualify the test, the data in interpolation into quarter so that the data into 60 observations. There are two variables used in this research, namely; private investment in both domestic and foreign investment and economic growth. To test the presence or absence of causality relationship between variables used Granger causality test. Granger test results show that there is no causality between the two directions of economic growth and investment in the city of Pontianak, but there is a unidirectional causality. Partially, investment is related to economic growth but there is no relationship between economic growth and investment.